All-fiber dual-wavelength fiber laser operating at 1950 nm region based on multimode interference effect - Azooz, S. M.; Jasim , Ali Abdulhadi; Hamida, Belal Ahmed; Ahmad , Harith B.; Harun, Sulaiman Wadi; Halder, Arindam; Paul, Mukul Chandra; Das, Shyamal; Pal, Mrinmay C.; Bhadra, Shyamal Kumar (National Institute of Optoelectronics, 2014)
An all-fiber dual-wavelength fiber laser operating at room temperature in 1950 nm region is reported. It uses a commercial Thulium-doped fiber (TDF) and homemade double-clad Thulium-Ytterbium co-doped fiber (TYDF) as gain media in conjunction with a multimode interferometer (MMI) filter in a ring configuration. The MMI filter consists of a 13.5 cm long MMF axially spliced at both its ends to identical single mode fibers to realize two transmission peaks at 1939.68 and 1959.60 nm with the maximum extinction ratio based on modal interference. By pumping the TDF and TYDF with a fixed 800 nm and 905 nm pumps at 143 mW and 1.5 W, respectively, dual-wavelength output lines are obtained at these two wavelengths with a signal to noise ratio of more than 27 dB, respectively. The dual-wavelength operation was stable for more than two hours and could be tunable since the laser wavelength is only determined by the function of the MMI filter.